Optimisation of the total harmonic distortions of the acoustic vacuum tube push-pull amplifier - MALECZEK, Stanisław (Archives of Acoustics, 2008)
The study presents the method of reducing total harmonic distortions of the acoustic vacuum tube amplifier with 30 W output power. The optimisation of the amplifier’s circuit is carried out by introducing the solutions applied in the transistor technology such as differential amplifiers with a source of a current. Selection of the amplifier vacuum tubes, as well as of their operating points, was studied as a mean to reduce the distortion amount of the whole amplifier stage. By optimising the amplifier it was presented how a simple circuit solution assures very good final parameters with relatively low costs. The measurements were conducted using the Audio Precision systems.